Subtype of atrial fibrillation and the outcome of transcatheter aortic valve replacement: The FinnValve Study - Jussi Jaakkola; Samuli Jaakkola; K. E. Juhani Airaksinen; Annastiina Husso; Tatu Juvonen; Mika Laine; Marko Virtanen; Pasi Maaranen; Matti Niemelä; Timo Mäkikallio; Mikko Savontaus; Tuomas Tauriainen; et al. (PUBLIC LIBRARY SCIENCE, 2022)
Whether the subtype of atrial fibrillation affects outcomes after transcatheter aortic valve replacement for aortic stenosis is unclear. The nationwide FinnValve registry included 2130 patients who underwent primary after transcatheter aortic valve replacement for aortic stenosis during 2008-2017. Altogether, 281 (13.2%) patients had pre-existing paroxysmal atrial fibrillation, 651 (30.6%) had pre-existing non-paroxysmal atrial fibrillation and 160 (7.5%) were diagnosed with new-onset atrial fibrillation during the index hospitalization. The median follow-up was 2.4 (interquartile range: 1.6-3.8) years. Paroxysmal atrial fibrillation did not affect 30-day or overall mortality (p-values >0.05). Non-paroxysmal atrial fibrillation demonstrated an increased risk of overall mortality (hazard ratio: 1.61, 95% confidence interval: 1.35-1.92; p<0.001), but not 30-day mortality (p = 0.084). New-onset atrial fibrillation demonstrated significantly increased 30-day mortality (hazard ratio: 2.76, 95% confidence interval: 1.25-6.09; p = 0.010) and overall mortality (hazard ratio: 1.68, 95% confidence interval: 1.29-2.19; p<0.001). The incidence of early or late stroke did not differ between atrial fibrillation subtypes (p-values >0.05). In conclusion, non-paroxysmal atrial fibrillation and new-onset atrial fibrillation are associated with increased mortality after transcatheter aortic valve replacement for aortic stenosis, whereas paroxysmal atrial fibrillation has no effect on mortality. These findings suggest that non-paroxysmal atrial fibrillation rather than paroxysmal atrial fibrillation may be associated with structural cardiac damage which is of prognostic significance in patients with aortic stenosis undergoing transcatheter aortic valve replacement.